Influence of hospital Accreditation on professional satisfaction of the nursing team: mixed method study - João Lucas Campos de Oliveira; Ana Maria Müller de Magalhães; Andrea Bernardes; Maria do Carmo Fernandez Lourenço Haddad; Lillian Daisy Gonçalves Wolff; Sonia Silva Marcon; Laura Misue Matsuda (Universidade de São Paulo, 2019)
ABSTRACT Objective: to analyze the influence of Accreditation on the professional satisfaction of nursing workers. Method: multicentric, cross-sectional research, outlined by the sequential explanatory mixed method. In the first preponderant, quantitative step, the validated Brazilian version of the Index of Work Satisfaction was applied to a sample (n = 226) representative of nursing professionals from three hospitals. One hospital was private and certified by Accreditation; another hospital was private and non-certified; and another was public and non-certified. By connection, the second step (qualitative) complemented the quantitative analysis. In this step, interviews (n = 39) were carried out and summarized through the method of Discourse of the Collective Subject. Descriptive and inferential statistical analyses were applied to the quantitative data connected to the qualitative support, as well as a joint presentation of part of the information in a joint display. Results: workers of the certified hospital had a better overall job satisfaction score. There were more statistical associations among workers in private hospitals. The comparison of the three groups investigated in the two steps of the mixed study confirmed Accreditation as a positive factor for professional satisfaction. The public hospital excelled in relation to the certified hospital in terms of salary, job requirements and interaction. Conclusion: Accreditation positively influenced the professional satisfaction of the nursing teams investigated.